Production of Polymer Blend from Algae and Polyethylene Blend - Muhammad Rusydi, Robaie (2012)
Polymer blends have properties similar to conventional plastics and tend to biodegradable by “natural” enzyme hydrolysis or chemical attack. Biodegradation is the breakdown of materials by the action of living organism. The objective of this project is to synthesis polymer blend from algae and polyethylene blend. The polymer blend is prepared by using extruder and hot press. There are five samples of polymer blends and contained algae from 0% to 20%. In order to determine the mechanical properties polymer blend, Universal Testing Machine (UTM) is used. The results showed that there are relation between tensile strength and composition of algae in polymer blend. When the composition of algae is increased, the tensile strength is decreased. The situation same with the percentage of elongation at break. The percentage of elongation at break is decreased when the percentage of algae is increased. For the biodegradability test which is water absorption testing, the percentages of water absorption of polymer blend is directly proportional to the composition of algae in polymer blend.